The female skier - Current insights and future directions - Strøm Solli, G. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
At the first Olympic Winter Games (OWG) in Chamonix in 1924, only 4% of the competitors were women. Female participation has steadily increased over the decades, rising to 20% at Squaw Valley in 1960, 30% at Lillehammer in 1994, 40% at the 2010 Vancouver Olympics, and is expected to reach 47% at the Milano Cortina 2026 OWG.1 Nordic skiing, a core component of cross-country skiing (XCS), biathlon (BIA), and Nordic combined (NC), will feature in 22% of the 116 total events and 60% of the 43 endurance events. Male XC skiers have competed in the OWG since its inception in 1924, but it wasn't until the 1952 Oslo Games that Lydia Wideman became the first female Olympic gold medalist in XCS. Biathlon saw its Olympic debut for men at the 1960 Squaw Valley Games, while women were first allowed to compete in 1992, with Anfisa Reztsova earning the first female Olympic gold in the discipline. Despite NC being part of the OWG for men since 1924, female NC athletes remain excluded and will not compete at the 2026 OWG.